Rethinking Gandhi and nonviolent relationality : global perspecti ves - Ganguly, Debjani; Docker, John. (London ; New York : Routledge, 2007)
This book presents a rethinking of the world legacy of Mahatma Gandh i in this era of unspeakable global violence. Through interdisciplinary research, key Gandhian concepts are revisited by tracing their genealo gies in multiple histories of world contact and by foregrounding their relevance to contemporary struggles to regain the "humane" in the midst of global conflict. The relevance of Gandhian notions of ahimsa and sa tyagraha is assessed in the context of contemporary events, when religi ous fundamentalisms of various kinds are competing with the arrogance a nd unilateralism of imperial capital to reduce the world to a state of international lawlessness. Covering a wide and comprehensive range of t opics such as Gandhi's vegetarianism and medical practice, his successe s and failures as a litigator in South Africa, his experiments with com munal living and his concepts of non-violence and satyagraha. The book combines historical, philosophical, and textual readings of different a spects of the leader's life and works. Rethinking Gandhi in a New World Order will be of interest to students and academics interested in peac e and conflict studies, South Asian history, world history, postcolonia l studies, and studies on Gandhi.
Based on presentations at a symposium on Gandhi held in late 2004 on the premises of the Humanities Research Centre at the Australian Natio nal University --T.p verso.
Includes bibliographical references and index.
Keywords: Gandhi, -- Mahatma, -- 1869-1948 -- Teachings -- Congresses; Gandhi, -- Mahatma, -- 1869-1948 -- Influence -- Congresses; Nonviolence -- Congresses; Civil disobedience -- Congresses